Tinjauan Faktor Keamanan dan Kerahasiaan Rekam Medis di Rumah Sakit TK.III DR. R. Soeharsono Banjarmasin - Handayani, Septy; Budiman, Arief (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2024)
The security of medical record documents involves risks and damage to the documents themselves. The aspects of damage mentioned include physical aspects, chemical aspects, biological aspects, and theft. The aim of this study is to assess the factors of security and confidentiality of medical record documents at Dr. R. Soeharsono Hospital TK. III. This type of research is qualitative descriptive. The sample in this study consists of 44 medical record documents involving 3 medical record personnel as respondents. Data was collected through observation using a checklist and interviews. The research results show that A4 paper with a weight of 70GSM (210x297 mm) and black ink with an oil-based type of ink are used. The highest damage to the documents occurred in the year 2019, with a total of 24 damaged files. The lighting conditions in the medical record room ranged from 40-99 lux, and the temperature in the medical record room ranged from 18?C - 28?C. There is a Light Fire Extinguisher (APAR) placed outside the medical record room. Two medical record documents experienced humidity. There were no reports of the presence of nuisance insects in the medical record room, and activities such as eating or drinking by personnel were found inside the room. Two medical record documents with faded patient names were discovered. Standard Operating Procedures (SOP) regarding security and confidentiality in the medical record room are available, and there is a warning at the medical record room's entrance prohibiting anyone other than medical record personnel from entering. The medical record room's door is always closed, but some medical record documents were found to be misfiled. There is no CCTV inside the room, and issues related to tracer were identified. Intrinsic factors are good, extrinsic factors are reasonably secure, and the confidentiality of medical records is maintained.